Karşılaştırma - Erenmemişoğlu, Burçak (Fen Bilimleri Enstitüsü, 1997)
Kavram olarak çok eskilere dayanan, ancak, terminolojide yerini son zamanlarda alan "Karşılaştırma", bir firmanın kendisini (süreçlerini, fonksiyonlarını, stratejilerini), rakipleri ya da konularında lider diğer şirketlerle kıyaslaması, bu konularda kendini geliştirmesi ve en iyiye ulaşmak için çalışmasıdır. Karşılaştırma' nın en önemli özelliği sürekli bir süreç olmasıdır. Bir şirketin başarılı olmasında en önemli faktör olan "Hızlı Öğrenme" Karşılaştırma çalışmalarıyla desteklenmelidir. Firmaların dört öğrenme şeklinden (başkalarından öğrenme, simülasyon, prototipleme ve deneyerek öğrenme) birisi olan başkalarından öğrenme, diğerlerine göre en düşük maliyete sahip olandır. Bir ülkenin endüstriyel gelişmesinde ve kalkınmasında önemli rol oynayan Karşılaştırma, sanayi casusluğu, tek yönlü bilgi alışverişi gibi amaçlarla kullanılmamalı ve böyle algılanmamalıdır. Karşılıklı bilgi alışverişi olarak değerlendirilen Karşılaştırma, geleceği şimdiden görmenin, gerekli atılımları yaparak geleceği bugünden yaşamanın ve firma için yeni bir gelecek yaratmanın en etkin yoludur. Gelecekte var olmanın yolu onu yaratmaktır. Varlığını sürdürmek ve lider olmak isteyen şirketler bilgiye sahip olmak, yeni bilgi yaratmak ve mükemmelliğe ulaşmak için öncelikle Karşılaştırma yapmak zorundadırlar. Elindeki bilgiyi paylaşmayıp ihtiyacı olan bilgiye ulaşmayan şirketlerin kroner damarlarındaki bu tıkanıldık geleceğe giden var olma yolunda ilerlemelerine engel olacaktır. Bu şirketler rakiplerin bugününü kendi gelecekleri olarak yakalamaya çalışacaklardır. Firmalarda karşılaştırma çalışmaları, organizasyonun çeşitli bölümlerinde çalışan kişilerden oluşan takım üyelerince ya da bu konuda danışman bir firmanın sorumluluğunda yürütülebilir. Her iki yöntemin de avantajları vardır. Günümüzde firmalar kendi elemanlarını yetiştirmek suretiyle bu çalışmaları sürdürmeyi tercih etmektedirler. Ancak, gün geçtikçe sayısı artan ve profesyonelleşen danışmanlık firmaları da bu alanda kısa zamanda yerlerini alacaklardır. Karşılaştırma çalışması, Karşılaştırma konusunun belirlenmesi, veri toplama, analiz ve uygulama adımlarından oluşan sürekli bir süreçtir. Bu adımların tek tek izlenmesi şart değildir, ama rehber olarak kullanılmalıdır. Bunun yanında her firmanın kendi iş akışına ve firma kültürüne göre bu akışı kendisine uyarlaması çalışmanın etkinliğini arttırmaktadır. Bu çalışma proses üretimi yapan, konusunda önder kısa süre önce birleşmesiyle oluşmuş bir şirkette yapılan uygulamadan örnek verilmiştir. Verilen örnekte firma içi Karşılaştırma projesi yürütülmüş ve sekiz ay içinde konulan hedeflere ulaşılmıştır.

Benchmarking is a process by which an organization continuously compares its processes, products and services to those of the world's best organizations with the same or similar functions. It is a comparative investigation that analyzes the gap between an organization's present level of performance and the best that exists. Finally, benchmarking is a way to study the methods of "best" organizations, to adapt their ideas, and to become, quickly and efficiently, the best in the world. Benchmarking is not new. Many companies have used it as a management tool for several decades. But 1980s witnessed a rebirth of benchmarking in a broader, more dynamic form. Previously, benchmarking referred to competitive analysis, industry analysis, performance benchmarks, functional benchmarks and other traditional techniques. These methods are still considered to be benchmarking, but many new elements have been added to the process. Led by Xerox, IBM, Motorola, 3 M and other companies, the re-emergence of benchmarking in a broader form has rekindled interest in its use. Many companies and organizations are finding that benchmarking can become a valuable means of improving their competitiveness and effectiveness. Benchmarking is becoming an integral part of their Total Quality Management system. This thesis describes the new, broader and more valuable benchmarking tool and how to apply it in an efficient, effective way. The examples are given from industry, but the process is applicable to education, government, health care, the military and other fields. Wherever organizations are under pressure to improve their processes, products and services, benchmarking offers a practical, affordable tool for becoming the best. Benchmarking has gained tremendous influence and currency in the 1990s. Correspondingly, front-line employees and operating managers have applied basic benchmarking skills in scores of different business situations. Among these applications, three distinct types of benchmarking have proliferated. They include : Process Benchmarking : This form of benchmarking seeks to identify the most effective operating practices from many companies that perform similar work functions (Customer complaint process, the billing process). Its power lies in its ability to produce bottom-line results. If an organization improves a core process, it can than quickly deliver performance improvements. These performance vm improvements may be calculated through increased productivity, lower costs, but their net effect frequently translates into improved short term financial results. Performance Benchmarking : Performance benchmarking enables managers to assess their competitive positions through product and service comparisons. Performance benchmarking usually focuses on elements of price, technical quality, product or service features, speed, reliability and other performance characteristics. Strategic Benchmarking: Strategic benchmarking roves across industries seeking to identify the winning strategies that have enabled high performing companies to be successful in their marketplaces. Strategic benchmarking influences the longer-term competitive patterns of a company. Organizations seeking short-term benefits usually find that process benchmarking produces results more rapidly. There are several distinct types of benchmarking in common use today: Internal Benchmarking : Comparing the process or function against a similar process, products, or services within organization. Sharing company confidential data should be easier. Competitive Benchmarking : Comparing the firm against the toughest external competitive organizations. Sharing data is not easy, but information that is gained can provide significant improvements. Functional Benchmarking : Comparing the firm against other world class companies who do what the firm does. These companies are often in the same general industry (e.g., electronics). These companies are more likely to share data than direct competitors. They are also a little more likely to have substantial improvement differences, but it will be a little harder to identify them. Generic Benchmarking : Comparing the firm to a world class company that is not even in same industry but that does some processes similar to firms. Consultant Study Benchmarking : Comparing the firm to any other world class company by utilizing the contracted services of a consultant. The major advantage of this method is that the consultant can act as an independent, neutral third party to collect and analyze sensitive data without diverting human resources from company. Benchmarking provides a powerful tool for Quality Management, Reengineering, Change Management concepts. Applying effective benchmarking process to these subjects, organization can achieve its goals quickly. Today, Total Quality Management is a means of improving service both to internal and external customers. The principles of Total Quality Management with regard to culture, organizational strategy and a documented quality management system all constitute the self improving organization. They all require commitment to training and education for the quality. Like other tools used in Quality program, Benchmarking has an extremely important role to play. Its primary purpose is the establishment and identification of areas of importance that may then be used as a IX channel for driving continuous improvement by closing the "Benchmarking Gap". Today, for many businesses, competition is on the world stage and in the crucial areas selected the only sensible goals are those which constitute world best practices. Benchmarking is a method for making sure that the targets aimed for are relevant to market demands. The path that brings company to Quality goes through the change. If organizations decide to approach the management of change in a systematic way, benchmarking is the most powerful tool within their grasp. By systematically studying others and comparing one's own operations and performance with the best and the most effective practices of successful companies, an organization can evaluate when change is necessity for market leadership. The on-going search for best practices quickly draws the company outside the confines of company's culture. Best practice benchmarking is therefore a pragmatic approach to managing change. Benchmarking should also be an integral part of strategy setting and strategic planning. A growing number of companies have begun to use benchmarking as a critical step in the strategic planning process. By reviewing the products, prices, practices, strategies, structures and services of competitors and other companies, managers can evaluate the adequacy of their own goals, plans and strategies. There are eight steps that an organization passes through during the strategic thinking process, and benchmarking can serve as an enabling tool to ensure the success of each step in the strategic planning process : Step 1: Analyze the organization's current profile. An organizational profile that includes current performance trends for all products and services, growth in all geographic areas, market share standing, the organizations core business concept or driving force, and areas of operating excellence. Step 2: Analyze internal and external performance variables. Examine the internal and external operating environments that positively or negatively influence future performance. Internal performance variables include key features of products, markets, customer segments, operating strengths, weaknesses, and growth opportunities. External performance variables include various competitive considerations, strategic opportunities and strategic threats, or operating vulnerabilities. Step 3: Explore driving forces and strategic options. Management must choose the best one or two strategic leverage points or driving forces and translate them into an integrated strategic mission, vision or operating plan. Step 4: Develop a tentative strategic profile for the organization. The profile identifies target markets and customer segments, defines corporate beliefs and values, delineates market size, growth rates, and expected investment returns and profit margins. Step 5: Develop competitive profiles. The organization's management assembles similar profiles for three or four major competitors, scrutinizing the competitor's products, services, pricing, and market selections. By examining competitor's profiles over a period of years, management can better anticipate the course each competitor is likely to pursue in the short-term future. Step 6: Test and evaluate the implications of the organization's proposed strategic course. By testing the organization's current profile, management can better assess the extent of change required to fulfill its strategic vision. The leadership wants to certain that important operating strengths are fully exploited, weaknesses are minimized, key beliefs are not violated, major opportunities are exploited, and major threats are avoided. Management also wants to match its strategic profile against competitor profiles to ensure that the organization's adopted strategy accurately reflects the competitor's strengths, weaknesses, and current and future actions. These strategic profile tests suggest how the organization's strategy can be modified and strengthened. Step 7: Finalize the strategic profile. At this step, management reshapes and fine- tunes the strategy by addressing issues that surface during the various tests conducted in Step six. Step 8: Resolve any remaining critical issues: In this final step of the strategic planning process, management resolves any critical issues surfaced through strategic profile analysis. Such critical issues include but are not limited to considerations of organizational structure, core operating systems, work force skills, and compensation systems. Benchmarking is not a afterthought of organizations that are highly skilled at strategic planning. It is not a one time event to fulfill a reporting requirement of the budget cycle. Quite the contrary, benchmarking is a hallmark of effective strategy development. It is an on-going enabler of strategic design, strategic planning, and strategic thinking. To raise the organization to championship class, benchmarking is a systematic process which aims at seeking excellence in the world in order to learn and adopt its operative content and processes. There are many ways that the organizations apply benchmarking process. One way of these effective ways of doing this process that can be a guide to companies is explained in this thesis in detail. Stage 1: Decide What To Benchmark : The object of the first stage is to identify what needs to be benchmarked in organization by analyzing and understanding customer's needs as well as the processes of business and its operative content. The whole organization can be benchmarked, as can its component parts, either from the internal standpoint of productivity or from the external standpoint of customer perceptions. Benchmarking exercises can be run on products, sales, production lines, customer service, quality systems, work routines and so on. There are in fact no limits except those set by customers' preferences and the needs of organization. The method of identifying what needs to be benchmarked is to study business and try to work out which areas are suitable candidates for benchmarking. Sometimes such areas are pretty well known before start, while in other cases it takes careful analysis of the business to narrow down and pinpoint the focus. In addition, it is often XI necessary to look outside the organization to identify areas suitable for benchmarking. Information may be needed from market about output of goods and services. A high volume of sales and good profitability may be result of short-term profit maximization and are not necessarily good indicators of quality. Creating a structural picture of business, and thinking hard about what its inherent components are, can often give an invaluable base on which to build benchmarking program. As far as possible, measurements and comparisons for critical performance factors should be done in quantitative terms. The commonest way to measure performance is to express the result in revenues, costs and profitability. Organizations should also decide the level of resolution at which the comparisons will be made. The most usual practice is to benchmark at three levels of resolution, starting with the whole then and then penetrating down into the organization in two stages. In a benchmarking project with the focus on productivity, the starting point may be to compare value-added productivity per employee. The next step is to break down the value-added term into its principal components, such as turnover, purchasing, personnel costs, overheads and capital costs, and express these for example as level of overheads per employee and so on. In the third step, organization can make a further breakdown of the business for in-depth understanding, and analyze such details as rental costs per employee. The first stage of benchmarking process, deciding what to benchmark, includes the following items: - What is the need and where does it exist in organization? - What do people outside organization think of organization's performance? - Survey the operations. - Using the method to explore. - Identify and learn the factors that are critical to performance and the units in which they can be measured. - Decide on the appropriate level of resolution for the study. Stage 2: Identify Benchmarking Partners: The purpose of the second stage is to identify, and establish relations with, companies and organizations that are recognized as "world champions" in the areas in which organization wants to compare its own performance. By calling them benchmarking partners, it is emphasized that relationship with them should be one of open exchange of information- not industrial espionage or anything of that nature. Under certain conditions it may be fairly easy to locate external organizations that represent excellence. There may be experience and knowledge in organization that can point to companies who fulfill the requirements of a benchmarking partner. News media and published reports can also give a fairly good idea of which companies or organizations would make good benchmarking partners. In other cases, the search for excellence may involve a systematic review of various types of business and industry. The second stage of the benchmarking process, identifying benchmarking partners, comprises the following steps: Xll - Decision on whether to run the study internally, within organization, or to compare organization with others outside it. - Search to find the companies that represent Best Demonstrated Practice. - Contact with benchmarking partners to secure their acceptance and collaboration. Stage 3: Gather Information : The purpose of the third stage, information gathering, is to supply the information needed for the analysis. It always starts in organization. There are two reasons for this. The first is that it teaches a great deal about businesses from the viewpoint and focus of what is to be benchmarked, and the second is that with business as a frame of reference precisely defined and specify what information is needed, thereby increasing both the precision of contacts with external partners and the guilty of the data. The third stage of benchmarking, information fathering, comprises the following main steps : - Draw up questionnaires, including definitions and explanations where necessary. - Collect information and compile data about business. - Collect information from benchmarking partner. - Collect information from other sources. - Document the information. - Check and verify the information to ensure that it is fully approved by responsible managers in both organization and benchmarking partner. Stage 4: Analyze : At first sight the mass of information may seem unstructured and impenetrable; the object of the fourth stage of benchmarking, analysis, is to bring order out of chaos. This fourth stage involves systematic sorting and organization of information and comparison of various measurement data with a view to identifying gaps in performance between operations and understanding the underlying operative contents and work processes which give insight into how the Best Demonstrated Practice companies achieve their excellence performance. The analytical phase also comprises documentation of the analytical results of the benchmarking study in a benchmarking report. This report is the document which contains the fact base on which rests the actual purpose of the study: to improve the performance of operations until they attain the level of excellence that is defined as Best Demonstrated Practice. As a result of study, some parts of operations may turn out to be doubtful; the question may arise of whether the company should continue with certain types of internal production at all, or whether the corresponding items should be bought from outside sources instead. To answer these questions, the operations concerned should be subjected to a make-or-buy analysis. The fourth, analytical stage of the benchmarking process thus comprises the following steps: - Sorting and organization of information and data. - Quality control of information. - Correction for non-comparable factors, if any. Xlll - Identification of performance gap to Best Demonstrated Practice and understanding of the underlying operative content that explains the existence of the gap- - Considering a make-or-buy analysis of dubious parts of the business. Stage 5: Implement for Effect: The fifth stage of the benchmarking process comprises the work of closing the gap which the analytical stage has identified, and translating the potential for improvement into tangible results. Measures must be taken to realize the potential that has been identified within the organization. The results of benchmarking study must be formulated as new goals for the business. These goals must then be broken down according to the chosen model, either in a process approach or in the regular line organization. When this has been, you must draw up a plan for implementation including specific plans for each part of the organization that will be affected. The fifth stage of benchmarking, implementation for effect, thus comprises the following steps: - Consider the implications of the results. - Integrate with the regular business plan. - Prepare a plan for changes to be made. - Implement the plan. Having taken part in a large number of implementation projects, some success factors have been identified: 1- Full management participation 2- Commitment 3- Understanding of corporate goals and strategies 4- Definite timetable and plan of action 5- Management concentration on the project 6- Information 7- Energy and perseverance Some managers may feel frustrated by the lack of standardization among benchmarking processes. Benchmarking experts, however, agree that no common benchmarking process standard is likely to establish itself soon. Corporate benchmarking managers contend that the benefits of a benchmarking process design that suits one's individual culture are far greater than the benefits of establishing a national process standard. They identify three motivating factors that throw the weight of benefits onto the side of each designing its own benchmarking process: 1- Customized benchmarking processes complement the individual corporate philosophy toward performance improvement. 2- Customized benchmarking processes support cultural differences among organizations. 3- Customized benchmarking processes accommodate the need for organizations to feel unique. Finally, a full list of benchmarking benefits cited by practitioners would reach as high as Everest. Bottom-line summaries almost always suggest that benchmarking: XIV - Improves organizational quality. - Leads to lower cost positions. - Creates buy-in for change. - Exposes people to new ideas. - Broadens the organization's operating perspective. - Creates a culture open to new ideas. - Serves as a catalyst for learning. - Increases front-line employees' satisfaction through involvement, empowerment, and a sense of job ownership. - Tests the rigor of internal operating targets. - Overcomes front-line employees' natural disbelief that they can perform better. Creates an external business view. Raises the organization's level of maximum potential performance. In the last chapter of this thesis, an example of benchmarking study from process industry is given. In this example, general stages of the application that was done in the production department, are explained. As this is a joint venture company, finding benchmarking partners and gathering information were done easily. Having full management participation, commitment and defining timetable, project team achieved goals. As it should be, benchmarking process in this company continued by setting new targets after the team achieved the goals.
Bencmarking
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 1997
Keywords: Karşılaştırma; Bencmarking